Apoio matricial e concepções sobre saúde mental a partir da perspectiva de profissionais da atenção básica - Moro, Larissa Moraes (2017)
This study aims to explore the work processes related to practices of mental health in services of primary health care network in Porto Alegre, as well as to analyze the conceptions and perspective of professionals of Primary Care about mental health. This is a qualitative, transversal and exploratory study. Data collection was performed from August to October 2016 in eight primary health care units: 1 traditional Basic Health service and 7 services with Family Health Teams (ESF). Research participants were 16 professionals: four physicians, five community health agents and seven nurses. The tool was semi-structured interviews, with a pre-elaborated script by researchers, which addressed issues related to work processes to mental health care. The interviews lasted approximately 40 minutes, which were recorded and transcribed. For data analysis, Thematic Analysis technique was chosen, according to Braun and Clarke. This research presents two articles. The first one aims to analyze the work processes in mental health from the perspective of the professionals of Primary Health Care of Porto Alegre, establishing similarities and differences in practices developed according to the mode of Matrix Support. Results show that the services with matrix support from Family Health Support Center demonstrated greater participation and integration of primary health care teams in mental health practices, and consequently, greater effectiveness and resilience of mental health care for users. The second article aims to analyze the conceptions and meanings attributed to mental health by professionals of primary care. Results show that the perspectives about the concept of mental health approach to the expanded understanding of health. This refers to a shift in the paradigm of mental health, which shows an advance towards an extended meaning of the concept, which reverberates in the consideration of social determinants of health.